Traditional uses of Medicinal Plants by Debbarma Tribes in West District Tripura, India - Saha, Poulami; Saha, Poushali; Debbarma, Chiranjit; Yadav, Gulab Singh (Indian Journal of Hill Farming, 2017)
A 36 ethno medicinal plant species, which includes 10 woody plants, 8 shrubs and 18 herbs used for different traditional herbal medicine formulations by Debbarma tribes in West Tripura district of Tripura. The knowledge on formulations of traditional herbal medicines were documented carefully with valid scientific nme, part(s) used, availability status, ailments and mode of preparation and use. The source of information is based on the personals interviews with local herbalist (Debbarma), aged tribal men and women.